Audit Energi Listrik Di SMK Negeri 2 Pontianak - ', Syahri (Faculty of Engineering, Universitas Tanjungpura, 2015)
Abstract– Electrical energy is very important in the world of education. It is very operational support in learning at SMK Negeri 2 Pontianak. Equipment such as air conditioning, lighting and a practice that is a lot of equipment that consumes electrical energy. This is a waste of energy. To tackle the problem of the energy efficiency. One of the methods that are now used for efficient energy consumption is energy conservation. Energy conservation is the increase in the efficiency of energy use or energy saving process. In this process include the presence of an energy audit that is a technique that is used to calculate the magnitude of the energy consumption in buildings and identify ways to penghematannya. On the study of energy Audit done on the building practices of SMK Negeri 2 Pontianak Activities performed include Energy Audits Energy Audits and Detailed Initial i.e. calculating the intensity of energy consumption (IKE) and looking for opportunities in energy saving building practice 2-lane Country SMK electricity into one substation with a capacity of installed 82.5 KVA From research results, obtained by IKE on a building which does not use the AIR CONDITIONING that is the building of practice techniques of automotive, electrical engineering and electronics engineering with the highest IKE 3,18 kWh/m²/month, this value includes the categories of wastes It needs to be done, to savings in this study, after saving the value of IKE to building practices that do not use the AIR CONDITIONING be 2.46 kWh/m²/month, this value includes the requirement of efficient compliance with the standards of the Ministry of national education Republic of IKE Indonesia for the requirement of efficient is 1.67 – 2.50 kWh/m²/month Keywords– Audit Of Energy, Intensity Of Energy Consumption